Dr Mahathir's selected letters to world leaders - Mahathir Mohamad Tun 1925- (Marshall Cavendish Editions, 2015)
Dr Mahathir Mohamad governed Malaysia for 22 years (1981-2003), during which he wrote and received many letters from many world leaders. The letters presented in this volume-by Dr Mahathir, Tony Blair, Bill Clinton, Lee Kuan Yew, Fidel Castro and Saddam Hussein, among others-argue the contrasting positions on bilateral and joint relations, globalization, as well as wars and conflicts. Dr Mahathir writes directly, in his own distinctive voice and style. The correspondents were transparent, solid, informative, and sometimes robust.